Highly efficient operation and uniform characteristics of curved mirror vertical-cavity surface-emitting lasers. (1st January 2023) - Ito, Maiko; Hamaguchi, Tatsushi; Makino, Tomohiro; Hayashi, Kentaro; Kearns, Jared A.; Ohara, Maho; Kobayashi, Noriko; Nagane, Shoetsu; Sato, Koichi; Nakamura, Yuki; Hoshina, Yukio; Jyoukawa, Tatsurou; et al.
Abstract: This study obtained highly uniform and efficient GaN-based vertical-cavity surface-emitting lasers with curved mirrors from a single wafer. The average threshold current ( I th ) and the optical output power ( P max ) of 14 chips measured up to 7.0 mA were 0.64 mA and 4.5 mW, respectively. The standard deviations of I th and P max were 6.7% and 5.1%, respectively. Additionally, the best chip showed maximum values of wall plug efficiency and output power of 13.4% and 7.6 mW, respectively, at 5.2 mA and 12.8 mA operating currents.